The Effect of Infant and Young Child Feeding (IYCF) on the Knowledge and Attitudes of Integrated Healthcare Center Cadres - Nanik Sudiyanti; Farida Nailufar; Diah Retno Wahyunigrum; Saraheni Saraheni (Media Publikasi Cendekia Indonesia, 2023)
This study aims to determine the effect of Infant and young child feeding training on the knowledge and attitudes of Integrated Healthcare Center cadres in Teluk Lingga, East Kutai Regency. The research is a quasi-experimental study with a pretest and posttest (one group pretest-postest) research design conducted in March 2023 in the working area of the Teluk Lingga Health Center, East Kutai Regency, East Kalimantan, Indonesia. A total of 51 cadres were involved as respondents by setting inclusion and exclusion criteria. IYCF variables are carried out by delivering material, counselors, and practices. The variables of knowledge and attitude were obtained using questionnaires that had been tested for validity and reliability. The data is then collected and then analyzed with the Paired-Sample T-Test. The difference in the level of knowledge of Integrated Healthcare Center cadres before and after being given IYCF training was 62.61 to 83.67 and obtained a p-value of 0.000. This means that there is an influence of IYCF training on the knowledge of Integrated Healthcare Center cadres. The attitude showed a difference in the attitude of Integrated Healthcare Center cadres before and after being given IYCF training with an average of 35.53, an increase of 42.96, and obtained a p-value of 0.000, which means that there is a significant difference between the average score on the pre-test and post-test. IYCF training has a significant effect on increasing the knowledge and attitudes of Integrated Healthcare Center cadres. We hope that this training will be carried out continuously.